IMPLEMENTASI ASESMEN KEBUTUHAN PESERTA DIDIK DALAM PENYUSUNAN PROGRAM BIMBINGAN DAN KONSELING BERBASIS NILAI ISLAM : STUDI LITERATUR (VARIABEL X : ASESMEN KEBUTUHAN PESERTA DIDIK, VARIABEL Y : PENYUSUNAN PROGRAM BK BERBASIS NILAI ISLAMI ) DI MADRASAH TSAN - Nadila Farahita; Lusia Juniarti; Hartini; Sumarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the integration of student needs assessment with the development of Islamic values-based guidance and counseling (BK) programs in madrasas. The study uses a qualitative approach using library research with data sources in the form of 24 primary and secondary literature consisting of books, national and international journal articles, and educational regulations published between 1995 and 2025, with the main focus on literature from 2012 to 2025. Data collection was carried out through documentation studies with stages of identification, selection, evaluation, and classification of literature according to the focus of the study. Data analysis used content analysis techniques (content analysis) interactive model Miles and Huberman which includes data reduction, data presentation, and drawing conclusions comparatively and thematically. The results of the study indicate that needs assessment is the main foundation in planning an effective and data-based BK program, but still tends to be value-neutral. On the other hand, the Islamic values-based BK program has proven effective in shaping the religious character of students, but has not been fully integrated with the results of the needs assessment. Therefore, an integrative model is needed that connects needs assessment as an empirical basis with Islamic values as a normative basis for developing guidance and counseling programs. This integration is crucial for producing guidance and counseling services that are more holistic, contextual, and aligned with the goals of Islamic education in madrasas.